Virtual Instrumentation: A way to Build Low Cost Laboratory Instruments - Fernando, H.T.T.M.; Sonnadara, D.U.J. (My University, 1998)
A detailed study on building virtual instruments using Personal Computers equipped with Sound Blaster cards was carried out. A computer with a Sound Blaster card can be used to create virtual instruments with a 44.1 KHz sampling rate and a 16-bit resolution. Our studies show that local laboratories and even schools can benefited by using instruments built with this technique since a computer with a Sound Blaster card can be converted to many instruments by simply changing the control system software. We were able to create a single channel digital storage oscilloscope without constructing any complex electronic circuits
Keywords: Instrumentation